CONTRACTIONS TO PLATELETS IN AORTAS OF CONTROL AND CHOLESTEROL-FED RABBITS - Verbeuren, T J; Van Diest, M J; Herman, A G (Thrombosis and Haemostasis, 1987)
Atherosclerotic aortas obtained from cholesterol-fed rabbits show a decreased responsiveness to noradrenaline, an increased responsiveness to low concentrations of serotoninand an unaltered responsiveness to prostaglandins. In vitro contractions induced by aggregating platelets are largely due to serotonin liberated during the aggregation. The present study was designed to compare the contractile responses to aggregating platelets inaortas obtained from control and cholesterol-fed rabbits.Male New Zealand rabbits were fed either a control or a 0.3% cholesterol diet during 16 weeks. Macroscopic and microscopic examination of the luminal surface of the aortas obtained from these animals revealed a substantial amount of fatty streaks in the tissuesobtained from the cholesterol-fed rabbits. Segments of the aortic arch of the rabbits were then mounted in organ chambers for isometric tension recording.In both the control and the atherosclerotic aortas increasing concentrations of platelets evoked contractions; the contractions obtained with the lower concentrations of platelets were significantly greater in the atherosclerotic tissues. The maximal responses and the ED50-values were comparable in both groups of blood vessels. No significant differences were observed when platelets obtained from control or hypercholesterolemic rabbits were compared. In the control and the atherosclerotic aortas the thromboxane receptorantagonist BM13505 at 2 x 10-5M did not significantly affect the contractionsto platelets obtained from either control or cholesterol-fed rabbits. The serotonin receptor antagonist ketanserin at 5 x 10-8M nearly abolished the responses to platelets in bothgroups of aortas.These experiments illustrate that (1) thecontractions induced by rabbit platelets in control and atherosclerotic aortas are mediated by serotonin and (2) the responses to platelets, as those to serotonin, are augmented in the atherosclerotic preparations.